Applying Non-Verbal Reinforcement in Increasing Students' Confidence in Economic Subjects - Febianti, Yopi Nisa; Gianti Nawangsari (Jurnal Pendidikan dan Pengajaran, 2024)
This study was motivated by students' low self-confidence in themselves and the environment, especially in teaching and learning activities in the classroom. This research aims to describe the level of student self-confidence in economics subjects by providing non-verbal reinforcement and the effectiveness of non-verbal reinforcement in increasing students' self-confidence during teaching and learning activities in economics subjects. With a high level of self-confidence, students can experience teaching and learning activities in class in a fun way which has an impact on increasing understanding of economic material. The research method used in this research is quasi-experimental. The population in this study was 146 students, and the sample was 36 students. Data collection in this research used tests and observations. The test in this study was used to measure students' self-confidence. Data were analyzed with descriptive statistics, percentages and t tests using SPSS. The research results showed that the effectiveness of implementing non-verbal reinforcement in increasing students' self-confidence increased after implementing non-verbal reinforcement. Before being given nonverbal reinforcement, students were in the less confident category when studying economics in class. Meanwhile, after being given non-verbal reinforcement, students experienced an increase in self-confidence when studying economics material in class. There is a significant difference in students' self-confidence after being given nonverbal reinforcement compared to before being given nonverbal reinforcement.